The Logic of Collective Rating - Nax, Heinrich H. (Frontiers in Physics, 2016)
The introduction of participatory rating mechanisms on online sales platforms has had substantial impact on firms' sales and profits. In this note, we develop a dynamic model of consumer influences on ratings and of rating influences on consumers, focussing on standard five-star mechanisms as implemented by many platforms. The key components of our social influence model are the consumer trust in the “wisdom of crowds” during the purchase phase and indirect reciprocity during the rating decision. Our model provides an overarching explanation for well-corroborated empirical regularities. We quantify the performance of the voluntary rating mechanism in terms of realized consumer surplus with the no-mechanism and full-information benchmarks, and identify how it could be improved.